Aceruloplasminemia: Waiting for an Efficient Therapy - Piperno, Alberto; Alessio, Massimo (Frontiers in Neuroscience, 2018)
Aceruloplasminemia is an ultra-rare hereditary disorder caused by defective production of ceruloplasmin. Its phenotype is characterized by iron-restricted erythropoiesis and tissue iron overload, diabetes, and progressive retinal and neurological degeneration. Ceruloplasmin is a ferroxidase that plays a critical role in iron homeostasis through the oxidation and mobilization of iron from stores and subsequent incorporation of ferric iron into transferrin (Tf), which becomes available for cellular uptake via the Tf receptor. In addition, ceruloplasmin has antioxidant properties preventing the production of deleterious reactive oxygen species via the Fenton reaction. Some recent findings suggest that aceruloplasminemia phenotypes can be more heterogeneous than previously believed, varying within a wide range. Within this large heterogeneity, microcytosis with or without anemia, low serum iron and high serum ferritin, and diabetes are the early hallmarks of the disease, while neurological manifestations appear 10–20 years later. The usual therapeutic approach is based on iron chelators that are efficacious in reducing systemic iron overload. However, they have demonstrated poor efficacy in counteracting the progression of neurologic manifestations, and also often aggravate anemia, thereby requiring drug discontinuation. Open questions remain regarding the mechanisms leading to neurological manifestation and development of diabetes, and iron chelation therapy (ICT) efficacy. Recent studies in animal models of aceruloplasminemia support the possibility of new therapeutic approaches by parenteral ceruloplasmin administration. In this review we describe the state of the art of aceruloplasminemia with particular attention on the pathogenic mechanisms of the disease and therapeutic approaches, both current and perspective.